Number of circulating pro‐angiogenic cells, growth factor and anti‐oxidative gene profiles might be altered in type 2 diabetes with and without diabetic foot syndrome. Issue 1 (6th September 2013) - Nowak, Witold N; Borys, Sebastian; Kusińska, Katarzyna; Bukowska‐Strakova, Karolina; Witek, Przemysław; Koblik, Teresa; Józkowicz, Alicja; Małecki, Maciej Tadeusz; Dulak, Józef
Abstract Aims/Introduction Type 2 diabetes is often complicated by diabetic foot syndrome (DFS). We analyzed the circulating stem cells, growth factor and anti‐oxidant gene expression profiles in type 2 diabetes patients without or with different forms of DFS. Materials and Methods Healthy volunteers (n = 13) and type 2 diabetes patients: (i) without DFS (n = 10); or with (ii) Charcot osteoneuropathy (n = 10); (iii) non‐infected (n = 17); (iv) infected (n = 11); and (v) healed ulceration were examined (n = 12). Peripheral blood endothelial progenitor cells (EPC), mesenchymal stem cells (MSC), hematopoietic stem cells (HSC) and very small embryonic‐like (VSEL) cells were phenotyped using flow cytometry. Plasma cytokine concentrations and gene expressions in blood cells were measured by Luminex and quantitative real‐time polymerase chain reaction assays, respectively. Results Patients with non‐complicated type 2 diabetes showed reduced HMOX1 expression, accompanied by HMOX2 upregulation, and had less circulating EPC, MSC or HSC than healthy subjects. In contrast, VSEL cells were elevated in the type 2 diabetes group. However, subjects with DFS, even with healed ulceration, had fewer VSEL cells, more CD45‐CD29+CD90+MSC, and upregulated HMOX1 when compared with the type 2 diabetes group. Patients with Charcot osteopathy had lowered plasma fibroblast growth factor‐2. Elevated plasma tumor necrosis factor‐α and decreased catalase expression was found in all diabetic patients. Conclusions Patients with type 2 diabetes and different forms of DFS have an altered number of circulating stem cells. Type 2 diabetes might also be associated with a changed plasma growth factor and anti‐oxidant gene expression profile. Altogether, these factors could contribute to the pathogenesis of different forms of DFS.